Tissue Type: A Crucial Factor Influencing the Fungal Diversity and Communities in Sichuan Pork Bacon - Zhang, Miao; Qiao, Haijun; Zhang, Weibing; Zhang, Zhongming; Wen, Pengchen; Zhu, Yan (Frontiers in Microbiology, 2021)
This study aimed to the variations of fungal diversity and community structure in different parts of traditional homemade Sichuan pork bacon. A total of seven phyla and 91 fungal genera were identified. Among them, Ascomycota and Basidiomycota were the first and second most abundant phyla in the bacon samples. In addition, five dominant genera (Debaryomyces, Aspergillus, Candida, Malassezia, and Penicillium) were shared by all bacon samples. The numbers of OTUs unique to individual groups were 14, 67, and 65 for the muscle tissue, the adipose tissue, and pork skin, respectively. Linear discriminant analysis showed that a total of 31 taxa signiﬁcantly differed among the groups. Results of Nonmetric Multidimensional Scaling and unweighted pair-group analysis indicated that physicochemical characteristics of bacon tissue were a major factor in shaping the bacon microbial communities. Results of network analysis also indicated that tissue type was a crucial factor influencing the fungal interactions in different samples. This study can lay a foundation for further isolation and identification of fungi in the product and provides a basis for further research of food ecology in homemade traditional pork bacon.